Creative character of religion in maintaining national identity among members of Belarusian ethic minority in Poland in democratic conditions - Sadowski, Andrzej (Creativity Studies, 2016)
The primary objective of this article is to shift a few hypotheses on the relationship between religion and nation. In the beginning of the article I present the interrelations between a religion and a nation being analyzed in the literature while trying to answer the question why nations need religion. Next, I present the role and importance of Orthodox Church in Poland, being the criterion of ethnicity affiliation for Belarusian national minority in Poland, particularly in the Podlaskie Voivodeship as the main area of residence for this community. In the nearest perspective, the Orthodox religion is likely to play a significant part in the process of forming Polish multi-ethnic and multinational creative society.